Macrophytes of the lowland wetlands in Morang district, Nepal - Koirala, Umesh; Jha, Sasinath (Nepalese Journal of Biosciences, 2013)
In total, 149 species of macrophytes (angiosperms 138, pteridophytes 7, bryophytes 2, algae 2) were recorded among which 117 species were emergent, 12 floating-leafed, 14 submerged and 6 free-floating on the basis of life form. In general, 68% species had flowering-fruiting during the rainy season, 17% in winter and 15% in the summer season. Many of the plant species were observed to play important role in meeting day to day requirements of the rural people. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7480 Nepalese Journal of Biosciences 1: 131-139 (2011)